Development of Tactical Thinking in Young Judokas through Competitive Situation Modeling - Kryvytskyi, Artur (Академічні візії, 2025)
This article examines the development of tactical thinking in young judokas through systematic modeling of competitive situations as a key component of modern sports training. The study emphasizes that tactical thinking in judo extends beyond the execution of techniques and includes the ability to analyze rapidly changing conditions, anticipate opponents’ intentions, and select the most effective actions under pressure. By recreating realistic fight scenarios during training sessions, athletes experience conditions that reflect the complexity and unpredictability of actual competitions, fostering the integration of physical preparedness, psychological resilience, and cognitive flexibility. Special attention is given to the pedagogical foundations of tactical preparation, including the design of situational exercises, the gradual increase in the complexity of training drills, and the use of feedback mechanisms for self-analysis and error correction. The study highlights that age-specific and individual characteristics of athletes must be considered to ensure consistent skill development and sustained motivation. It also emphasizes the role of situational modeling in improving decision-making speed, stress tolerance, and strategic adaptability, which are essential for achieving success in high-level competitions. In addition to pedagogical and psychological aspects, the article discusses practical issues related to integrating competitive modeling into training programs, such as balancing simulated and real fights, applying innovative coaching methods, and using interdisciplinary knowledge from sports psychology, pedagogy, and biomechanics. The findings confirm that systematic modeling of competitive situations enhances both technical and tactical proficiency and contributes to the holistic development of young athletes. Finally, the paper outlines directions for future research, including the implementation of digital technologies, video analysis, and interactive training tools to further improve tactical learning processes. These approaches can significantly increase the effectiveness of sports training and help prepare judokas to compete successfully at national and international levels.